SEJARAH PERKEMBANGAN ILMU GENETIKA - Akbar Satrio; Endang Noventiyani; Intan Tamara; Nur Azizah; Yonas Irwanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the historical development of genetics from the pre-Mendelian era to the age of modern genomics. Genetics, as a branch of biology, has advanced progressively through a series of major scientific discoveries, beginning with early observations of inherited traits, the formulation of inheritance laws by Gregor Mendel, the identification of chromosomes, the establishment of DNA as the genetic material, and the emergence of contemporary gene-editing technologies. This research employed a literature study method by reviewing accredited national journals published in 2023 and relevant national textbooks. The analysis was conducted through topic identification, content analysis, and the synthesis of a chronological narrative on the evolution of genetic science. The results indicate that the development of genetics has been driven not only by biological discoveries but also by technological innovations that enable deeper molecular analysis. The findings highlight the importance of understanding the history of genetics as a foundation for advancing biotechnology, healthcare, agriculture, and biology education. This study recommends strengthening genetic research in Indonesia and enhancing genetics education through practical work and the integration of modern technologies.